The introduction of mandatory audit firm rotation in the EU: the case of Portugal - Pinto, D. (2020)
A central issue in audit regulation is whether the introduction of mandatory audit firm rotation enhances audit quality. This paper contributes to the ongoing debate surrounding this issue by analyzing how senior auditors of one of the Big Four accounting firms in Portugal perceive the policy. This study adopts a qualitative methodology based on semi-standardized interviews. In general terms, the interviewees perceive mandatory audit firm rotation negatively due to the loss of client-specific knowledge it causes, the limited association between audit independence and tenure, and the resulting decrease in fees potentially harmful to audit quality